Produção, caracterização e avaliação in vitro de filmes finos de vidro niobo-fosfato por deposição a laser pulsado - Sanz, Carolina Kaminski (2017)
Implant osseointegration is related to the implant surface’s ability to create strong and direct chemical bonds with adjacent bone tissue. Surface treatments are a way to obtain these surface properties. Among the different treatments, bioactive materials coatings stand out. In this work, thin niobo-phosphate bioactive glass (CaF2-CaONb2O5-P2O5) films were deposited by pulsed laser deposition (PLD) on Ti substrates aiming to enhance its bioactivity and osseointegration. Samples were analyzed by SEM, EDS, XPS, XRD, XRF, AFM, profilometry, scratch test, focal contact and cell proliferation and differentiation. In XPS analysis, CaNb2(P2O6) and NbOx structures were found. Crystalline phases were not identified on the films, since the glass has an amorphous structure. Together, these results suggest that both material synthesis and deposition are reproducible. It was possible to deposit thin bioactive glass films on titanium by PLD, there was stoichiometric transfer from the target to the films and, after the deposition, the material’s glassy structure was maintained. In vitro tests did not reveal statistically significant differences between deposited films and the Ti control samples, even though samples deposited with 50 mJ showed an increase in cell quantity, and samples deposited with 100 mJ presented better cell spreading.